2020
DOI: 10.1021/acs.iecr.0c02352
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Catalytic Degradation of Antibiotic Molecules by 2D Sheets of Spinel Nickel Ferrite

Abstract: Pharmaceutical wastes such as antibiotics in the industrially polluted water are hazardous for the aquatic ecosystem and the environment and, hence, need to be adequately treated. Prompt and efficient degradation makes the microwave (MW) technique a cutting edge technology. Apart from promptness and efficiency, the ideal MW catalysts need to be thermally robust, recyclable, and economic. The coprecipitation synthesized highly crystalline spinel nickel ferrite (SNFO, E g ∼1.76 eV, M s ∼20 emu/g) and zinc ferrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…CoFe 2 O 4 NS of 20 nm exhibit the properties of a permanent magnet at room temperature . Highly crystalline spinel NiFe 2 O 4 and ZnFe 2 O 4 are reported as highly active catalysts under microwave irradiation for water remediation . The use of different capping agents such as oleylamine and triethanolamine during the solvothermal synthesis of Co x Mn 3– x O 4 led to changes in the morphology and composition from cubic Co 2 MnO 4 nanorods to tetragonal CoMn 2 O 4 microspheres, while the absence of a capping agent resulted in tetragonal CoMn 2 O 4 cubes .…”
Section: Recent Advances In Metal Ferrite Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…CoFe 2 O 4 NS of 20 nm exhibit the properties of a permanent magnet at room temperature . Highly crystalline spinel NiFe 2 O 4 and ZnFe 2 O 4 are reported as highly active catalysts under microwave irradiation for water remediation . The use of different capping agents such as oleylamine and triethanolamine during the solvothermal synthesis of Co x Mn 3– x O 4 led to changes in the morphology and composition from cubic Co 2 MnO 4 nanorods to tetragonal CoMn 2 O 4 microspheres, while the absence of a capping agent resulted in tetragonal CoMn 2 O 4 cubes .…”
Section: Recent Advances In Metal Ferrite Nanostructuresmentioning
confidence: 99%
“…29 Highly crystalline spinel NiFe 2 O 4 and ZnFe 2 O 4 are reported as highly active catalysts under microwave irradiation for water remediation. 31 The use of different capping agents such as oleylamine and triethanolamine during the solvothermal synthesis of Co x Mn 3−x O 4 led to changes in the morphology and composition from cubic Co 2 MnO 4 nanorods to tetragonal CoMn 2 O 4 microspheres, while the absence of a capping agent resulted in tetragonal CoMn 2 O 4 cubes. 32 A recent study by McDonald showed the MgFe 2 O 4 NS of 10 nm size can be synthesized using the rapid microwave and used for photocatalytic application.…”
Section: Recent Advances In Metal Ferrite Nanostructuresmentioning
confidence: 99%
“…Mishra et al [125] found that nickel ferrite (SNFO) and zinc ferrite (SZFO) were good microwave absorbers. They degraded 90 % and 86 % of tetracycline hydrochloride (TCH) in 15 minutes, respectively.…”
Section: Microwave Assisted Heat Treatmentmentioning
confidence: 99%
“…Mishra et al [125] . found that nickel ferrite (SNFO) and zinc ferrite (SZFO) were good microwave absorbers.…”
Section: Technologies Of Treating Wastewater Polluted By Pharmaceutic...mentioning
confidence: 99%
“…4). [48][49][50][51][52] It should be noted that the interaction of the catalyst with CIP is necessary and for this adequate adsorption (chemisorption is better) is needed. The surface area will determine the accessibility of the catalyst surface and therefore is one of the most important factors determining the overall efficiency.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%